Dede Korkut'un Delileri - Kocakaplan, İsa (My University, 2004)
Bu makalede, Türk Edebiyatının önemli eserlerinden biri olan Dede Korkut Kitabında yer alan “deli” unvanlı tipler üzerinde durulacaktır. Söz konusu tipler ve davran›fl biçimleri ekseninde, “alp” tipinden “alperen” tipine geçerli gösteren ip uçlar› değerlendirilecektir. Dede Korkut hikayeleri islam öncesi alp tipinden, islam sonrası alp-eren tipine geçişi gösteren ilginç örnekleri taşımaktadır. Bu hikayelerde “deli” kelimesi “kendi gücüne aşırı şekilde güvenen ve korkusuzca –bazen şuursuzca- hareket eden kahramanlara verilen bir unvan olarak karşımıza çıkmaktadır. Ancak Deli Dumrul ve Deli Karçar örneklerinde görüldüğü üzere onların maddi güçleri, kendilerini aşan bir manevi güç tarafından denetim alt›na alınır. Hikâyelerdeki bu tercihin, toplumda güç sahibi olanlarda, kendilerinden güçsüz kimselere karşı adaletli davranma duygusunu geliştirme amacına yönelik olduğu söylenebilir.

In this article, we’re going to dwell upon the type of heroes called “deli” (brave, hero, mad, crazy) as featured in Dede Korkut, one of the most important tomes of Turkish Literature. We’re going to evaluate the clues showing the transition from the “heroic/alp” type to the “heroic-dervish/alperen” type on the abovementioned axis of types and their ways of behaviour. Dede Korkut stories include interesting samples which show the transition from heroic/alp type before Islam to heroic-dervish/alperen type after Islam. In these stories the word “deli” denotes the title which is given to the heroes who have overconfidence in their own power and behave fearlessly, and at times unconsciously. But in the examples of Deli Dumrul and Deli Karçar their physical power is controlled by a spiritual power which is beyond their control. It’s possible to say that this preference in these stories aims to incline people with high status in society to behave justly toward the people with less power than themselves.
Keywords: Türk Edebiyatı; Türkiye; Türk Folkloru; Hikaye; Turkish Literature; Turkey; Turkish Folklore; Story